Role of obstetric colour doppler studies in predicting perinatal outcome in pregnancy induced hypertension - Mishra, Ritu; Misra, Aditya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy induced hypertension (PIH) is associated with adverse perinatal outcome. Multi vessel colour Doppler studies are useful in these cases for timely intervention. The aim of present study was to know the significance of umbilical, middle cerebral and uterine artery Doppler in PIH and to analyse their role in predicting perinatal outcome. Methods: This is a study of 150 pregnant women with pregnancy induced hypertension (PIH). These patients were evaluated with colour Doppler and were followed subsequently for any adverse perinatal outcome. Results: Out of 150 cases 70% of cases were found in 20-30 years age group. 98 cases had abnormal uterine artery Doppler indices accounting for 65.3%, while 52 cases had a normal Doppler index accounting for 34.3%. Out of 150 cases, 94 (64.6%) cases had abnormal middle cerebral artery. In our study 53 cases had abnormal umbilical artery Doppler indices accounting for 35.4%, while 97 cases had a normal Doppler index accounting for 64.6%. Out of 150 cases in our study 27 cases had Reversal of a wave in ductus venosus waveform that is in 18%. In this study total 5 cases (35.7%) of perinatal mortality were seen. Conclusions: The knowledge of various doppler parameters may help to improve pregnancy outcome and identification of PIH at earliest gestation age as compared to other antepartum test modalities.